C-reactive protein (CRP) promotes malignant properties in pancreatic neuroendocrine neoplasms. Issue 7 (July 2019) - Schimmack, Simon; Yang, Yongchao; Felix, Klaus; Herbst, Markus; Li, Yixiong; Schenk, Miriam; Bergmann, Frank; Hackert, Thilo; Strobel, Oliver
Abstract : Objective: Elevated pre-operative C-reactive protein (CRP) serum values have been reported to be associated with poor overall survival for patients with pancreatic neuroendocrine neoplasms (pNEN). The aim of this study was to identify mechanisms linking CRP to poor prognosis in pNEN. Methods: The malignant properties of pNENs were investigated using the human pNEN cell-lines BON1 and QGP1 exposed to CRP or IL-6. Analyses were performed by ELISA, Western blot, flow cytometry and immunocytochemistry as well as invasion and proliferation assays. To compare cytokine profiles and CRP levels, 76 serum samples of pNEN patients were analyzed using Luminex technology. In parallel, the expression of CRP and growth signaling pathway proteins was assessed on cell lines and paraffin-embedded primary pNEN. Results: In BON1 and QGP1 cells, inflammation (exposure to IL-6) significantly upregulated CRP expression and secretion as well as migratory properties. CRP stimulation of BON1 cells increased IL-6 secretion and invasion. This was accompanied by activation/phosphorylation of the ERK, AKT and/or STAT3 pathways. Although known CRP receptors – CD16, CD32 and CD64 – were not detected on BON1 cells, CRP uptake of pNEN cells was shown after CRP exposure. In patients, increased pre-operative CRP levels (≥5 mg/L) were associated with significantly higher serum levels of IL-6 and G-CSF, as well as with an increased CRP expression and ERK/AKT/STAT3 phosphorylation in pNEN tissue. Conclusion: The malignant properties of pNEN cells can be stimulated by CRP and IL-6 promoting ERK/AKT/STAT pathways activation as well as invasion, thus linking systemic inflammation and poor prognosis.